The Impact of Covid-19 Lockdown on Working Capital Management and Profitability of Firms: A Case Study of Lesley Bakers PVT LTD - Wadesango, Ongayi; Jones, Victor; Sitsha, Lovemore; Wadesango, Newman (International Journal of Economics and Financial Issues, 2022)
This research study was carried out to analyse the impact of Covid-19 Lockdown towards working capital management and profitability of companies. The main complications faced were loss of market whilst operational costs remained on the same level. Enforcement of lockdown regulations such as curfews and intercity travel bans posed a threat in profit statuses of many firms. A challenge also faced was reduction of workforce to meet World Health Organisation requirements of social distancing and health safety protocols. The researchers applied quantitate descriptive research design to gather data from the baker’s employees. Questionnaires were used to collect data. Lesley was driven by the conservative approach techniques whereby it was required to reduce receivables from customers, maintaining high stocks, and timely settlement of liabilities. However, following the covid-19 global pandemic which led to many business operations being ceased and many of the organisation’s clients which are in the formal sector to be highly affected resulting in the delaying of amounts due. The sudden increase in debtors would result in cash shortages to fund other operations and pay the current liabilities. Furthermore, the findings indicated slow payment by credit customers meaning that most of the firm’s accounts receivable remains outstanding for a long period of time. This is evidenced by high percentages of accounts receivable compared to other current assets of the firm. The researchers found that effective working capital management techniques had to be applied to continue operations. The researchers recommend companies to minimize their operational, production and capital expenditure in response to reduced market forces. Government support should be granted to local firms since they are no longer importing materials or exporting products, whilst the firm apply efficient working capital techniques.